Analysis of Intrinsic Elements of the Novel Athar Cinta Dalam Ikhlas by Abay Adhitya: Analisis Unsur Intrinsik Novel Athar Cinta dalam Ikhlas Karya Abay Adhitya - Govinda, Govinda; Ahada Wahyusari; Legi Elfitra (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Intrinsic elements are elements of a fictional story that are directly within, become part of and help shape the existence of the story in question. The intrinsic elements contained in a fictional story are intended to form a story. One of them is the intrinsic element contained in Athar's novel Cinta Dalam Ikhlas. This research aims to describe the intrinsic elements contained in the novel Athar Cinta Dalam Ikhlas. The research method that researchers use is descriptive qualitative. The analytical technique used in analyzing the novel Athar Cinta Dalam Ikhlas is the listening and note-taking technique. The instruments used in this research were the researchers themselves and data inventory tables as supporting instruments. The results obtained in this research are intrinsic elements (1) the theme of a journey of love full of secrets from god’s destiny (2) backward plot because the character”i” in the story tells his journey and lift experisinces (3) the setting in the roam, yerd, cemetery, schools. Night, morning, afternoon settings. The setting is a sad, silent, tense, and uncertain atmosphere (4) story building characters with 2 main charakters (athar and Ara) and 4 supporting characters (Mama, Pak Farhan, kang Zein, and Mamat) and 5 implied message never forget good because everything that happens which is our destiny is all his will.